Rural tourism policies in Malaysia: transcending unidirectional to a multi-directional policy-cycle - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (2014)
Success and sustainability of rural tourism depends on the role of government agencies in formulating policies, practices and delivering services. The Malaysian government recognises the need to reduce instances of economic diaspora through rural tourism by narrowing the income disparity gap, alleviate poverty and preserving the cultural and natural heritage of the rural community. Rural tourism policies in Malaysia include, but not exhaustive to, The Rural Tourism Master Plan and The National Ecotourism Plan. The policy cycle is a mean of analysing public policy formulation that provides a series of sequential stages influencing the growth and scientific rationality in policy studies. The stages of a policy cycle include agenda setting, policy formulation, policy adoption, implementation and evaluation. However, unidirectional policy-cycles have limitations. This would include the requirement of policy-makers to go through a series of stages before it can be improved and amended. This process can be time consuming, which causes the policy to be out-dated by the time it reaches the end-user. The objective of this paper is to investigate the use of a multidirectional policy-cycle that would allow timely interventions, amendments and improvements that can be conducted at the particular stage when the gap is identified.